Ingkar Sunnah Dalam Perspektif Pemikiran Ibn Hazm Al-Andalusī - Yogi Juliansyah; M. Syahrul; Zikri Darussamin (CV. ITTC INDONESIA, 2025)
The phenomenon of denial of the Sunnah, namely the rejection of the authority of hadith as a source of Islamic teachings, has become a crucial issue in contemporary hadith studies. Although it emerged more strongly in the modern era, the seeds of similar thinking have been criticized by classical scholars. Ibn Hazm al-Andalusi (d. 456 AH) is one of the important figures who emphasized the position of hadith in the structure of Islamic law. Through his monumental work, al-Iḥkām fī Uṣūl al-Aḥkām. This study aims to highlight the importance of this Andalusian scholar's contribution to maintaining the methodological foundations of Islam. The method used in this study is qualitative with a literature study approach, examining Ibn Hazm's texts and comparing them with discourses on denial of the Sunnah in both classical and modern traditions. The results show that Ibn Hazm not only rejected the attitude of denial of the Sunnah but also offered a systematic framework of ushul fiqh to maintain the authority of hadith. These findings emphasize the relevance of Ibn Hazm's thought to contemporary discourse, particularly in facing the wave of criticism of hadith. Thus, this study highlights the importance of the contributions of Andalusian scholars in maintaining the continuity of Islamic epistemology.